THE USER SATISFACTION LEVEL WITH THE CONVENIENCE OF FACILITIES IN MOSQUES IN KUCHING, SARAWAK: A PERSPECTIVE FROM FACILITY MANAGEMENT - Juwita Zaidi; Adibah Yusuf; Faridah Sahari; Khairul Aidil Azlin Abdul Rahman; Shaikh Azahar Shaik Hussain; Nangkula Utaberta (Journal of Islamic Architecture, 2023)
Facility management is a way to ensure that an organization's buildings are well-maintained and aligned with the organization's goals. The purpose of this study is to determine the level of visitor satisfaction with mosque facilities. The Sarawak State Mosque, Kuching City Mosque, and Kuching City Indian Mosque were selected as the study locations. A questionnaire survey was used to achieve the research objective, with mosque visitors as the target respondents to answer the questionnaire. The survey data was analyzed using descriptive analysis methods. The study findings indicate that the overall level of visitor satisfaction at the mosques is good. Visitors find that the facilities provided at each mosque are in good condition and meet their needs.